Experience of using ICT tools for monitoring the psychological component of the quality of teacher's activity of the higher education institutions - Bondarchuk, Olena I.; Balakhtar, Valentyna V.; Balakhtar, Kateryna S.; Kyrichuk, Valeriy O.; Yakubovska, Nataliia O.; Ostapov, Serhii E.; Grubi, Tamara V. (Serhiy Semerikov, 2022)
The focus of the current research is on the quality of education as a multifaceted category, and the monitoring of the quality of education – as a purposeful and specially organized system of studying, assessment, analysis of data on the state of education of students. Emphasis is on the psychological component of monitoring the quality of education, which involves creating a positive socio-psychological atmosphere for participants in the educational process, both students and teachers. Creating a comfortable atmosphere allows teachers to perform their work effectively, and higher education institutions – implement the main task of ensuring the quality of teaching staff. The article highlighted the experience of monitoring the psychological component of the quality of higher education using various ICT tools – Google services, specially created websites for professional psychological diagnostics, author’s programs of psychological testing (“Comprehensive diagnosis of psychosocial development of the teacher’s personality using a computer program “Personnel – Ψ””), etc. This study aims to study current conditions, namely the development of digital technologies. The need to use electronic resources (Google services) has increased, which allows you to create text documents, presentations, spreadsheets, forms, drawings, programs and other documents. In order to provide the monitoring of the quality of the psychological component of higher education teachers’ activity, Google Forms was elaborated to obtain information about the psychological state and satisfaction with the quality of educational services by the participants of the educational process, their relationship, the socio-psychological climate in higher education and others, amongst to respond to social and educational change on time.
Keywords: Quality of Education; Monitoring of the Quality of Education; Psychological Component of the the Quality of Education; ICT Tools; Psychodiagnostic